Ancient Religions, Modern Politics - Michael Cook (Princeton University Press, 2014)
news will have noticed that ancient religions play a significant part in modern politics. These religions are not, however, by any means interchangeable in their political roles. Most obviously, it is hard to miss the fact that Islam today has a higher political profile than any of its competitors. But why should that be so? Is there something about the formal or substantive character of the Islamic tradition that makes its invocation an attractive option for Muslim individuals and groups that are politically active in a modern contextâ€”something that is not found in other religious traditions? Is there a reason why one can understand the contemporary politics of India and Latin America perfectly well without having heard of such medieval luminaries as MÄdhava and Aquinas, whereas one cannot hope to understand the politics of the contemporary Islamic world without having heard of Ibn Taymiyya? This is a major question about the world we live in, but my sense is that much of the literature on the politics of the Islamic world tends either not to attend to the issue or to deal with it rather crudely. In this book I attempt to respond to the question with at least a partial answer. To do this I have approached the Islamic case in a comparative setting. I thus seek to compare the role of Islam in modern politics with the parts played by Hinduism and Christianityâ€”the latter mainly in the Latin American context. That I picked this particular pair is in some measure accidental, but there is also a certain logic to it: I wanted heritages to which large Third-World populations owe allegiance. This does not prevent me from referring occasionally to such faiths as Judaism and Sikhism, but I make no attempt to include them in a systematic way. The methods I employ throughout are those of a historian, since these are just about the only ones I know how to use. I would hope, however, that my disciplinary readership will not be limited to historians. Thus, political scientists may find some of the book of interest, though it will not attempt to emulate the methodological rigors of their discipline. So also may those engaged in the academic study of religion, though they may find my treatment rather philistineâ€”my subject, after all, is religion in politics, not religion in itself. But I would also hope that the book will be accessible, and have some illumination to offer, to reasonably determined readers coming to it with nothing more than an interest in one or another of the relevant aspects of world affairs.